INTEGRASI TEOLOGI KRISTEN DAN NILAI BUDAYA LOKAL DALAM PEMBENTUKAN KEPEMIMPINAN TRANSFORMATIF GEREJAWI - Uci Raya; Niar; Kasuaran; Grace luluanti; Agustina (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyze and describe the integration of Christian theology and local cultural values ​​in the formation of transformative church leadership in Indonesia. This integration is crucial because the church lives and serves in diverse cultural contexts, so effective leadership needs to be rooted in Christian faith while being relevant to the social realities of society. Through a descriptive qualitative approach with a review of theological and cultural literature, this study found that local cultural values ​​such as mutual cooperation, deliberation, moral responsibility, and solidarity align with the leadership principles taught by Christ, namely love, service, and sacrifice. Contextualizing theology through local cultural values ​​does not mean changing the substance of the Gospel, but rather presenting it in a relevant and communicative manner for the congregation. Furthermore, this study demonstrates that transformative church leadership born from the synthesis of theology and culture has the potential to build an inclusive, adaptive, and transformative church.